Shucked : original Broadway cast recording [compact disc] - Horn, Robert; Clark, Brandy (Musician); McAnally, Shane (Masterworks Broadway, 2023)
What do you get when you pair a semi-neurotic, New York comedy writer with two music superstars from Nashville? A hilarious and audacious farm-to-fable musical about the one thing Americans everywhere can't get enough of: corn. Features music by Brandy Clark and Shane McAnally.